Person detection from surveillance camera - Bai, Lu (Nanyang Technological University, 2020)
Surveillance is a part of security. In most cases, this work costs a lot of time for people to observe and discover abnormal behaviors. Fortunately, the camera is the tool that can assist us to do this time-spending work. Compared to humans, the machine has a better vision. However, there is a doubt whether the detection performance of the machine is as accurate as that of human-being.